Teaching Skills for math teachers in middle school (Journal of the College of Basic Education, 2022)
The research aims to identify the teaching skills of mathematics teachers in the intermediate stage. The research sample consisted of (150) teachers and teachers in some schools affiliated to the General Directorate of Education in Baghdad / Rusafa ll The researcher relied on preparing the teaching skills scale on previous studies and literature. Use the (T) test and Pearson correlation coefficient to compare the results. The results resulted in:There is a statistically significant difference at the level of significance (0.05) between the arithmetic average and the hypothetical mean for the degrees of teachers of mathematics in the teaching skills scale and in favor of the arithmetic mean There is a positive correlation between the mathematics teachers ’grades and the mathematics teachers’ grades in the Teaching Skills Scale . In the light of the results of the research, the researcher concluded that the level of mathematics teacher’s performance was good in the scale of teaching skills and recommended a number of recommendations and proposals